Serum levels of cytokines (TNF-α, IFN-γ& IL-10) in Type-2 diabetic patients with HCV infection - Saour, May Y.; Saleh, Eman M.; Mall-Allah, Zena T. (Journal of the Faculty of Medicine Baghdad, 2011)
Back ground: Type 2 Diabetes mellitus (T2D) is a common complication of all liver diseases. However clinical and experimental data suggest a direct role of HCV in the perturbation of glucose metabolism. The aim of this study is to investigate the role of HCV infection as a risk factor to develop type 2 diabetes mellitus, and to study the immunopathogenicity of HCV in diabetes mellitus patients, through the assessment of IFN-γ, TNF- α and IL-10 serum levels. Objectives: Is to investigate the role of HCV infection as a risk factor to develop type 2 diabetes mellitus, and to study the immunopathogenecity of HCV in diabetes mellitus patients, through the assessment of IFN-γ, TNF- α and IL-10 serum levels. Patients and Methods: Thirty six known T2D patients attending the endocrine and diabetes center in Baghdad for check-up were enrolled in this study. Their age ranged from 15- 70 year. Twenty one patients have T2D only while the other Fifteen were have diabetes with HCV infection. Thirteen healthy individuals without any signs or symptoms of disease were also included in this study as healthy controls. Serum levels of cytokines including IFN- γ, TNF-α and IL-10 were analyzed by ELISA immunoassay. Results: Higher serum levels of IFN-γ and TNF-α were observed in the investigated HCV patients with diabetes (43.87pg/ml, 68.1pg/ml respectively) compared to T2D patients (19.75 and 55.10 pg/ml respectively) and controls (8.08 and 31.4 pg/ml respectively). The statistical analysis revealed a significant difference between these three groups (P= 0.01). The mean serum levels of IL-10 were significantly elevated in T2D group as compared to HCV patients with T2D and control groups (28.7, 10.32, 15.78 pg/ml respectively, p=0.05). Conclusion: The over production of proinflammatory cytokines (IFN-γ, TNF- α) and the low IL-10 level could play a crucial role in pathogenesis of HCV that leads to T2D via increasing the insulin resistance.